The Geographic Origins of Ethnic Groups in the Indian Subcontinent: Exploring Ancient Footprints with Y-DNA Haplogroups - Mahal, David G.; Matsoukas, Ianis G. (Frontiers in Genetics, 2018)
Several studies have evaluated the movements of large populations to the Indian subcontinent; however, the ancient geographic origins of smaller ethnic communities are not clear. Although historians have attempted to identify the origins of some ethnic groups, the evidence is typically anecdotal and based upon what others have written before. In this study, recent developments in DNA science were assessed to provide a contemporary perspective by analyzing the Y chromosome haplogroups of some key ethnic groups and tracing their ancient geographical origins from genetic markers on the Y-DNA haplogroup tree. A total of 2,504 Y-DNA haplotypes, representing 50 different ethnic groups in the Indian subcontinent, were analyzed. The results identified 14 different haplogroups with 14 geographic origins for these people. Moreover, every ethnic group had representation in more than one haplogroup, indicating multiple geographic origins for these communities. The results also showed that despite their varied languages and cultural differences, most ethnic groups shared some common ancestors because of admixture in the past. These findings provide new insights into the ancient geographic origins of ethnic groups in the Indian subcontinent. With about 2,000 other ethnic groups and tribes in the region, it is expected that more scientific discoveries will follow, providing insights into how, from where, and when the ancestors of these people arrived in the subcontinent to create so many different communities.